2007
DOI: 10.1080/14789940701443173
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating innovative treatments in forensic mental health: A role for single case methodology?

Abstract: The rapid development of new forensic mental health services and treatments has created a demand for research and evidence relating to the effectiveness of interventions. Unfortunately, the literature on outcomes of treatments for mentally disordered offenders is sparse, compared with the substantial 'what works' literature regarding non-disordered offenders in the criminal justice system. In this paper we propose that single case research methodologies have a part to play in remedying this unsatisfactory stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…One of the most obvious findings of the literature review was the limited treatment literature in forensic mental health, an observation which has also been noted by other writers (e.g., Davies, Howells, & Jones, 2007;Hillbrand & Young, 2008). This may reflect the specialty's early stage of development and the emphasis, until quite recently on assessment-related issues including risk to others, legal classification and disposition, and the role of expert witness.…”
Section: Paucity Of Literature On Interventionmentioning
confidence: 78%
“…One of the most obvious findings of the literature review was the limited treatment literature in forensic mental health, an observation which has also been noted by other writers (e.g., Davies, Howells, & Jones, 2007;Hillbrand & Young, 2008). This may reflect the specialty's early stage of development and the emphasis, until quite recently on assessment-related issues including risk to others, legal classification and disposition, and the role of expert witness.…”
Section: Paucity Of Literature On Interventionmentioning
confidence: 78%
“…Current thinking on treatment evaluation now includes a much greater emphasis on measuring change through individual case formulation and monitoring of individual change (Davies et al, 2007) as well as more traditional group-based tests of treatment effectiveness. …”
Section: Discussionmentioning
confidence: 99%
“…Whilst these studies are not indicative of level of met or unmet need, they raise the notions of treatment intensity and frequency ('dosage'), service responsivity (how well specific service user needs are met) and how these relate to a timely care pathway. Within Broadmoor Hospital, amongst service users with complex and multiple needs, the challenge of reducing the average length of stay from 8 years was considered to be most appropriately met through the provision of a needs-responsive service which was clearly based on an individualised case formulation and monitoring of individual change (Davies, Howells and Jones, 2007). This in turn required clarity about met and unmet needs of the service users and the development of more logically sequenced, timely and relevant interventions in order to provide a comprehensive and streamlined pathway through the hospital.…”
mentioning
confidence: 99%
“…While it would evidently be unwise to over-generalize in such a context, it is nevertheless hoped that the following account might offer a modest illustration of how theory and practice have the potential to illuminate and synergize each other within the crucible of clinical practice. Nevertheless, despite this cautionary caveat, it is worth observing that in specialities such as forensic practice (in which the total number of patients treated is inevitably small) the single case study approach has been identified as being of particular value for enhancing our knowledge of how to work more effectively with these complex individuals (Davies et al, 2007).…”
Section: General Introductionmentioning
confidence: 99%